Upaya Peningkatan Pembelajaran Sastra Anak Melalui Pemanfaatan Media Audio Visual Pada Siswa TK Tunas Ceria Trimoharjo - Herni fitriani; Zulfa Sofiana; Hera Dita Triwidianingsih (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve children's literature learning in kindergarten students through the use of audio-visual media. This activity was carried out at Tunas Ceria Trimoharjo Kindergarten involving students and teachers. The method of this activity includes teacher training in utilizing and using audio-visual media, mentoring the implementation of the use of media in literature learning, and evaluating student involvement and understanding. The results of the activity showed a significant increase in student interest in learning literature, understanding of story content, retelling skills, creativity in expression, and involvement in discussions. The use of audio-visual media has been proven to increase student interest in the learning process, improving student understanding in appreciating literary works. The use of audio-visual media is a technology-based learning medium that requires supporting facilities such as projectors, speakers, and laptops so that the learning process can run well.